Knowledge Management and Public Value in Municipal Mergers: The Nuova Pescara Case - Fabio Zuccarini; Alberto Trinchini; Simone Cifolelli; Andrea Ziruolo (European Conference on Knowledge Management, 2026)
Municipal mergers are commonly examined through their effects on administrative efficiency, expenditure, and service delivery. Yet, their success also depends on the capacity to integrate the knowledge, competences, routines, and institutional memories embedded within previously autonomous organizations. This paper reconceptualizes municipal amalgamation as a knowledge-intensive organizational transformation and investigates how Knowledge Management (KM) can support organizational integration and Public Value co-creation. The study adopts a conceptual research design supported by an exploratory case study of Nuova Pescara, one of the largest municipal merger processes currently underway in Italy. Drawing on documentary and institutional evidence, the analysis interprets the merger’s as-is, to-be, and gap analysis phases through the lenses of Knowledge Management, Organizational Learning, and Public Value. The findings suggest that administrative integration should be understood as the outcome, rather than the starting point, of a progressive knowledge integration process. Building on these insights, the paper develops a Knowledge Integration Governance Framework in which knowledge transfer, combination, and creation, supported by organizational learning and Strategic Human Resource Governance, transform distributed knowledge into shared organizational capabilities. The study contributes to Knowledge Management research by positioning knowledge integration as a strategic governance capability enabling institutional transformation and creating the organizational conditions for Public Value co-creation.